Synergistic effect of B and Y on the isothermal oxidation behavior of TiAl-Nb-Cr-V alloy. (February 2018) - Gong, X.; Chen, R.R.; Fang, H.Z.; Ding, H.S.; Guo, J.J.; Su, Y.Q.; Fu, H.Z.
Highlights: The addition of B and Y improved the oxidation resistance at 900 °C effectively. The adhesion of oxide scale was enhanced after adding B and Y. B and Y inhibited the formation of harmful vanadium oxides and TiO2 . B and Y promoted the selective oxidation of Al atoms. Abstract: Isothermal oxidation was conducted at 900 °C to investigate the synergistic effect of B and Y on the oxidation behavior of Ti44Al6Nb1Cr2 V alloy. The results indicated that Ti44Al6Nb1Cr2V0.15Y0.1 B possessed superior oxidation resistance. B and Y refined the crystalline particles size and reduced the oxygen activity. As a results, the formation of TiO2 and vanadium oxides was suppressed. The reduction of dissolved oxygen in the alloy promoted the selective oxidation of Al. Meanwhile, oxide pegs were formed at the interface of oxide scale and Ti44Al6Nb1Cr2V0.15Y0.1 B alloy. Therefore, the spalling resistance of the oxide scale was enhanced by adding B and Y.